The chloroplast genome sequence of Commelina communis (Commelinaceae) - Yong Cui; Rifan Liang (Mitochondrial DNA. Part B. Resources, 2019)
Commelina communis is a hyperaccumulator on heavy metal with high drought resistance and endurance. Using Illumina next-generation sequencing data, its chloroplast genome is assembled and characterized. The complete chloroplast genome is 159,664 bp in length, consisting of a pair of inverted repeats (IRs) of 26,146 bp each, an 88,854 bp large single-copy (LSC) region and an 18,518 bp small single-copy (SSC) region. It has 137 genes in total, comprising 81 unique protein-coding genes, 32 unique tRNA genes, and 7 rRNA genes. Phylogenetic analysis based on the complete chloroplast genome sequences indicates that C. communis is sister to Belosynapsis ciliata among species with available chloroplast genome sequences.